Jeřábová kočka - Dvorník, Milan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Bakalářská práce se zabývá návrhem pojezdového mechanismu jeřábové kočky mostového jeřábu o požadované nosnosti 20 000kg a pojezdové rychlosti 0,6m.s-1. Cílem práce je navrhnout koncepci řešení pojezdového mechanismu a následné provedení technických výpočtů zaměřené na návrh pojezdového kola, pohonu (elektromotor, brzda a převodovka), hnací hřídele a vybraných komponent (pera a ložiska). Součástí práce je i výkresová dokumentace.

The bachelor thesis is concerned with design of drive mechanism for bridge travelling crab with demanded load 20 000kg and travelling speed 0,6m.s-1. The objective of work is design a solution concept of the drive mechanism and subsequent performance technical calculations focused on a running wheels, drive (electric motor, brake and gear-box), drive shaft and chosen parts (couplings and bearings). Part of this thesis is also the drawing documentation.
Travelling crab
Keywords: Jeřáb; jeřábová kočka; pojezdový mechanismus; elektromotor; převodovka; Crane; travelling crab; drive mechanism; electric motor; gear-box